‘A dismal howling’: Formulaic density and the Gothic tableau - Aguirre, Manuel (Adam Mickiewicz University, 2021)
Scant attention has been paid by critics to the formulaic diction that pervades the Gothic genre. This article continues an extended experiment aiming to analyse formulaicity in one of the less-known Gothic novels. Peter Teuthold’s 1794 The Necromancer exhibits massive co-occurrence: textual units (lexemes, sounds, and both phrase and clause formations) regularly gravitate around other textual units, effectively clustering into fields. A field is defined as an open paradigm of items related by functional equivalence; the novel handles its components not as independent units but only in accordance with a ‘fielding’ principle, that is, only as paradigmatic elements which can be exchanged for or combined with other elements. Previous work has established a distinction between the formula properly so called and the formulaic pattern, defined as a construct that attracts lexical, phonological, syntactic, and connotative fields into its orbit. The article argues that ‘fielding’ operates on at least one ‘higher’ level, the level where formulaic patterns combine to shape a charged moment in the narrative – a tableau. After selecting a fragment of text and illustrating the structure of a single formulaic pattern, the article isolates each phrase or clause segment in the fragment, outlines the pattern it belongs in, and shows that over seventy-five per cent of its textual matter is demonstrably formulaic. Analysis of several other excerpts suggests that formulaic density is not homogeneous but decreases or rises at different points in the novel. A rationale for high-density segments is then sought in the ritualising nature of the tableau itself.
Keywords: co-occurrence; field; formulaic pattern; Gothic fiction; liminality; overpatterning; ritualisation; tableau